Development module collaborative guidance counseling service socio-emotional in early childhood - Dwi Afri Yani; Anita Yus; Aman Simaremare (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to test the effectiveness of the collaborative counseling service information module in improving children's socio-emotional development in early childhood at RA Azrina, Medan Marelan. The research method used is research and development (RnD) using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The study included 20 early childhood children, with teachers and parents serving as assessors of the children’s socio-emotional development. Data were collected through observation, interviews, and questionnaires, and a paired-samples t-test was used to assess the effectiveness of the implemented module. The results showed that the application of this information service module significantly enhanced children’s socio-emotional development. Statistical tests indicated a significant difference between pretest and posttest scores from teachers and parents, suggesting that collaboration between teachers and parents in using the module played a vital role in the development of children’s socio-emotional skills. This research emphasizes the importance of strengthening collaboration between parents and teachers to support children's socio-emotional development in early childhood education. Additionally, this module can serve as a reference for the development of similar programs in other early childhood education institutions. Abstrak Penelitian ini bertujuan untuk menguji efektivitas modul layanan informasi bimbingan konseling kolaboratif dalam meningkatkan perkembangan sosial emosional anak usia dini di RA Azrina, Medan Marelan. Metode penelitian yang digunakan adalah penelitian dan pengembangan (RnD) dengan model ADDIE, yang terdiri dari analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian ini adalah 20 anak usia dini, dengan guru dan orang tua sebagai penilai perkembangan sosial emosional anak. Data dikumpulkan melalui observasi, wawancara, angket, serta uji paired sample t-test untuk mengukur efektivitas modul yang diterapkan. Hasil penelitian menunjukkan bahwa penerapan modul layanan informasi ini memberikan dampak signifikan dalam meningkatkan perkembangan sosial emosional anak. Berdasarkan hasil uji statistik, terdapat perbedaan yang signifikan antara nilai pretest dan posttest yang diberikan oleh guru dan orang tua, yang mengindikasikan bahwa kolaborasi antara guru dan orang tua dalam menggunakan modul tersebut berperan penting dalam pengembangan keterampilan sosial emosional anak. Penelitian ini memberikan implikasi penting mengenai perlunya penguatan kolaborasi antara orang tua dan guru dalam mendukung perkembangan sosial emosional anak di PAUD. Selain itu, modul ini dapat dijadikan referensi untuk pengembangan program serupa di lembaga pendidikan anak usia dini lainnya. Kata Kunci: bimbingan konseling; kolaborasi; PAUD; perkembangan sosial emosional